The Relationship Between Maternal Education, Family Income, Parenting Style, and Language Development in Children Aged 3-4 Years in Boyolali, Central Java - -, Muryanti; Dharmawan, Ruben; Murti, Bhisma (Indonesian Journal of Medicine, 2016)
Background: Early childhood is a unique period where development proccess such as language development occurs rapidly.ÃÂ  Speech and language disorders are two among the most common problems in children. The first years of life form critical period in childrenÃ¢â¬â¢s life. Maximum brain plasticity occurs during the initial years of life and continues to develop for a few years with slower pace. Sensorik experience, stimulation, and language exposure during this period determine the synaptogenesis, myelinisation, and synaptic relation. National Center for Health Statistics (NCHS) reported that speech disorder ocurred approximately 0.9% in children under five, and 1.94% in children aged 5-14 years old. The purpose of this study was to determine the relationship between maternal education, family income, parenting style, and language development in children aged 3-4 years.Subjects and Method: This was an analytic observational study with cross sectional design. This study was conducted at Kindergarten Nogosari Sub-district, Boyolali, Central Java. A sample of children aged 3-4 years old were selected for this study. The dependent variable was language development. The independent variables were maternal education, family income, and parenting style. The data were analyzed by multiple logistic regression.ÃÂ Results: Maternal education Ã¢â°Â¥ high school (OR= 25.74; 95% CI= 1.80 to 367.62; p= 0.017), family income Ã¢â°Â¥ minimum regional wage (OR= 32.98; 95% CI= 2.93 to 370.52; p= 0.005), and democratic parenting style (OR= 20.19; 95% CI= 1.83 to 222.82; p= 0.014), had positive and statistically significant relationships with language development in children aged 3-4 years old.Conclusion: Maternal education Ã¢â°Â¥ high school, family income Ã¢â°Â¥ minimum regional wage, and democratic parenting style, have positive and statistically significant relationships with language development in children aged 3-4 years old.Keywords: maternal education, family income, parenting style, child language developmentCorrespondence: Muryanti. School of Health Polytechnics, Poltekkes Surakarta. Email: muryanti.tw@gmail.comIndonesian Journal of Medicine (2016), 1(2): 100-107https://doi.org/10.26911/theijmed.2016.01.02.03